The ultrafine powder of atractylodis macrocephalae rhizoma improves immune function in naturally aging rats by regulating the PI3K/Akt/NF-κB signaling pathway - Yu, Wang; Jie, Su; Su, Gao; Zhuangwei, Niu; Yiqing, Zhou; Suhong, Chen; Guiyuan, Lv (Frontiers in Pharmacology, 2025)
BackgroundThe phenomenon of population aging presents a significant global challenge, with the aging population in China steadily increasing. As individuals progress in age, there is a gradual deterioration of human organs and systems, as well as a decline in the immune system, referred to as immunosenescence. Atractylodis macrocephalae rhizoma (BZ) has been historically used in China for its medicinal properties, including gastrointestinal improvement, immunomodulation, anti-aging, antioxidant effects, and anti-tumor effects. Nevertheless, there remains a gap in understanding the pharmacological and molecular mechanisms underlying its anti-immunosenescence effects.MethodsThis study employed UPLC-ESI-MS and network pharmacology to create a network map of BZ ultrafine powder (BZU) and its aging targets. Enrichment analysis was then used to identify the primary mechanistic pathways underlying BZU’s anti-immunosenescence effects. The primary components of BZU were quantitatively analyzed using high-performance liquid chromatography (HPLC). Naturally aging rats were used to examine the effects of different oral doses (0.25, 0.5, and 1 g/kg) of BZU over 5 weeks on aging performance, peripheral blood immunophenotyping and cell count, and splenic lymphocyte proliferation rate. To validate the findings of network pharmacology, quantitative RT-PCR, Western blotting, and immunofluorescence analyses were conducted.ResultsOur analyses demonstrated that BZU improved various indicators of aging in naturally aging rats, such as increasing the number of voluntary activities, enhance grip strength and fatigue resistance, increasing the microcirculatory blood flow and improving hematological levels. The BZU administration enhanced T and B lymphocyte proliferation and significantly improved the lymphocyte-to-T cell subpopulation ratio. It can elevate serum IL-2 and IL-4 levels while reducing IL-6, IFN-γ and TNF-α levels in naturally aging rats. Finally, it increased CD3 protein expression in the spleen while decreasing protein levels of PI3K, p-AKT, IKKα/β, and NF-κB. It also decreased the mRNA expression of Pik3cg, Akt1, Pdk1 and Nfκb1.ConclusionThese findings suggest that BZU may enhance lymphocyte proliferation by inhibiting the PI3K/Akt/NF-κB signaling pathway, correcting immune cell imbalances, reducing inflammatory responses, and ultimately enhancing immune function and potentially delaying aging.